Impact of rainfall onset date on crops yield in Ghana - Kumi, Naomi; Adeliyi, Tolulope E.; Asante, Vincent A.; Abiodun, Babatunde J.; Lamptey, Benjamin L. (Frontiers in Sustainable Food Systems, 2023)
Rainfall onset is relevant for farmer planting decisions yet there is less information on the extent to which this decision influences crop yield. This study assesses the effect of rainfall onset date (ROD) on the yield of four crops (Maize, millet, rice, and sorghum) in Ghana. It uses crop yields from the Ministry of Food and Agriculture (MoFA) and the Food and Agriculture Organization (FAO), and employed the Decision Support System for Agro-technology Transfer (DSSAT) crop model to simulate maize yields from 1985 to 2004, using weather data from the gridded Global Meteorological Forcing Dataset (GMFD). RODs from three datasets (observed, satellite, and GMFD) were compared in relation to crop yields. The results show a good agreement between the RODs (correlation coefficient of 0.72 between observed and satellite, and 0.32 between observed and GMFD), and also the MoFA and FAO data (i.e., correlation coefficient of 0.97, 0.92, 0.77, and 0.99 for maize, millet, rice, and sorghum, respectively). The satellite and GMFD data replicate the observed interannual variability of RODs albeit with some biases. This study also found a good relationship between observed RODs and crop yield, where early onset corresponds to high yield for most of the selected crops. The satellite data replicates a similar pattern for all the crops but the GMFD indicates an early onset correspondence with low yields for millet and sorghum. The DSSAT model is able to reproduce the observed yield pattern realistically, but with significant biases. The findings of this study can be used to advise small-holder farmers on planting dates and crop variety selection.